2018
DOI: 10.1371/journal.pone.0195362
|View full text |Cite
|
Sign up to set email alerts
|

The impact of routine data quality assessments on electronic medical record data quality in Kenya

Abstract: BackgroundRoutine Data Quality Assessments (RDQAs) were developed to measure and improve facility-level electronic medical record (EMR) data quality. We assessed if RDQAs were associated with improvements in data quality in KenyaEMR, an HIV care and treatment EMR used at 341 facilities in Kenya.MethodsRDQAs assess data quality by comparing information recorded in paper records to KenyaEMR. RDQAs are conducted during a one-day site visit, where approximately 100 records are randomly selected and 24 data element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 34 publications
7
42
0
1
Order By: Relevance
“…Improvement in data accuracy observed from these assessments implies that the regular data quality assessments may have contributed positively to data accuracy and is consistent with ndings from repeated data quality audits conducted elsewhere [17][18][19]. Other contributors to improved data accuracy could be regular supportive supervision and shift to electronic reporting that were introduced simultaneously with the DQA.…”
Section: Discussionsupporting
confidence: 73%
“…Improvement in data accuracy observed from these assessments implies that the regular data quality assessments may have contributed positively to data accuracy and is consistent with ndings from repeated data quality audits conducted elsewhere [17][18][19]. Other contributors to improved data accuracy could be regular supportive supervision and shift to electronic reporting that were introduced simultaneously with the DQA.…”
Section: Discussionsupporting
confidence: 73%
“…The few attempts to measure antibiotic use in primary care in LMICs have relied on reviews of prescription and sales records, simulated clients or observed encounters 7. The use of routine data to measure and improve quality of primary healthcare delivery, while common in high-income countries,32 is rare in LMICs 20. The Guidelines Adherence in Slums Project has pioneered the use of rubber stamp templates and smartphones to deliver routine data on primary care delivery in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…While computer-based electronic medical record (EMR) systems are used to provide routine data on clinical care in high-income countries, paper is still a commonly used interface for documentation in LMICs 18. Besides the challenges of implementing EMR systems in low-resource settings,19 little is known about the quality of data entered into electronic systems in LMIC contexts 20. The recent revolution in access to mobile technologies provides a great opportunity to reach and support frontline health workers in LMICs 21.…”
Section: Introductionmentioning
confidence: 99%
“…EMR is efficient because it provides many features and supports the use of WSN. EMR is defined as a one-organization system [39]. Currently, most Australian professionals use an EMR, which is rated similarly in several countries such as Germany, New Zealand, and the Netherlands [40].…”
Section: Overview Of Techniques Used In Reisch • Electronic Medical Rmentioning
confidence: 99%